Comparative Chemical Composition of n-Hexane and Ethanol Extractives from The Heartwood of Black Locust - Khalil Hosseinihashemi, Seyyed; Safdari, Vahidreza; Kanani, Siavash (Asian Journal of Chemistry, 2012)
In this study, extractives from the heartwood of Robinia pseudoacacia L. (black locust), which was cultivated in the arid region of Iran, were obtained by two steps of extraction. In one step of extraction, fresh wood meal sample was inserted in a balloon and its extractives have been eliminated with n-hexane solvent. In the second step of extraction, the extracted wood meal residue was inserted in ethanol solvent at ambient temperature. The chemical compositions of two extractives were analyzed by gas chromatography-mass spectrometry (GC/MS). The comparison extraction extracts has shown that the major components in the n-hexane extract mainly to be contained the hexadecanoic acid, trimethylsilyl ester (13.39 %), (Z,Z)-9,12-octadecadienoic acid (10.10 %), tetradecane (6.88 %), bis(2-ethylhexyl)phthalate (6.21 %) and hexadecane (6.15 %), while the major components in the ethanol extract are resorcinol (51.96 %), (Z,Z,Z)-9,12,15-octadecatrien-1-ol, (6.27 %), hexadecanoic acid (6.06 %) and (Z,Z)-9,12-octadecadienoic acid (4.08 %). The same components present in the two different extracts also contained amounts of the octadecane, hexadecanoic acid, ethyl ester, (Z,Z)-9,12-octadecadienoic acid, linoleic acid ethyl ester and (Z,Z,Z)-9,12,15-octadecatrienoic acid.